La presunción de inocencia frente a la prisión preventiva, en el proceso penal ecuatoriano. - Moran, Eddy J. (2022)
The article elucidates, from a theoretical, doctrinal and jurisprudential study, whether or not the precautionary measure of preventive detention violates the constitutional guarantee of presumption of innocence, assured for the benefit of all persons; and, if possible, within the scope of a constitutional State of rights and justice, the coexistence of the two legal institutions, within the framework of the criminal process, without affecting fundamental rights. In the doctrinal sphere, there has been a deep criticism of the validity of preventive detention, considering it an “anticipated penalty”, which affects the presumption of innocence. A position that confronts two positions: one, which seeks to guarantee the right to be treated as innocent, which protects any person suspected of committing a possible crime; and, the other, seeks to combat impunity, ensuring the end of the criminal process. Hence the importance of finding, through a study, a balance between the presumption of innocence and the effectiveness of criminal justice. The research approach is qualitative, because it is a study of the current legal reality; analyzing, under the deductive method, the doctrinal foundations, which support each of the theses in confrontation. Documentary type research, which is supported by the data collection technique, contained in texts related to the topic addressed. It comes to the conclusión that the application of preventive detention does not represent an anticipated sentence; therefore, it is a necessary measure (procedural instrument) and does not violate your right to the presumption of innocence.